2013
DOI: 10.1590/s1415-43662013001000011
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento das isotermas de adsorção do pó da polpa de manga liofilizada

Abstract: RESUMOA qualidade e a vida útil dos pós de frutas dependem de seus teores de água e da maneira como esta se encontra ligada ao alimento. O comportamento higroscópico de alimentos em pó pode ser avaliado através de suas isotermas de sorção. O objetivo deste trabalho foi avaliar modelos matemáticos para representação da isoterma de sorção do pó de manga liofilizada e avaliar as características físico-químicas da polpa de manga in natura e seu pó liofilizado. Foram feitas as análises de umidade, pH, sólidos solúv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 20 publications
6
27
0
13
Order By: Relevance
“…Similarly, Oliveira et al (2011) observed higher moisture content in the molecular monolayer (Xm) for the model of BET, for the lyophilized sapodilla powder. Moreira et al (2013) also observed increase in temperature as a predominant factor for the increment of moisture contents in the monolayer (Xm) through the models of GAB and BET, similar to the result of the present study.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, Oliveira et al (2011) observed higher moisture content in the molecular monolayer (Xm) for the model of BET, for the lyophilized sapodilla powder. Moreira et al (2013) also observed increase in temperature as a predominant factor for the increment of moisture contents in the monolayer (Xm) through the models of GAB and BET, similar to the result of the present study.…”
Section: Resultssupporting
confidence: 91%
“…Moreira et al (2013) claim that this reduction in C values is expected and cite that low temperatures favor the force of interaction between adsorbate-adsorbent, favoring an increment in the values of the constant C. Figure 1 shows that the obtained isotherm is of type III, according to the classification of Braunauer (Andrade et al, 2011). The typical form of an isotherm reflects the form in which it connects to the system, so that the weaker interactions with water molecules generate higher water activity; thus, the product becomes more unstable (Andrade et al, 2011).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In the model of Oswin, the lowest value of the constant 'a' (17.5067) and highest value of 'b' (0.5943) were obtained at the temperature of 30 ºC, which was also observed by Moreira et al (2013), analyzing the hygroscopic behavior of mango powder obtained through lyophilization. According to Alcântara et al (2009), for a good representation of the adsorption isotherms of a food, the values of the parameter 'a' in the Oswin model must be higher than zero and those of 'b' must be between zero and 1.0; this model satisfactorily fitted to the experimental data.…”
Section: Resultsmentioning
confidence: 55%